2000
DOI: 10.2165/00002018-200023040-00003
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine

Abstract: Quetiapine, a dibenzothiazepine derivative, is a atypical antipsychotic which has greater in vitro binding affinity for serotonin 5-HT2 receptors than for dopamine D2 receptors. Quetiapine effectively treats both the positive and the negative symptoms of schizophrenia and is also associated with an incidence of extrapyramidal symptoms no greater than placebo across the entire dose range. In addition, it does not cause persistent hyperprolactinaemia. Quetiapine is associated with high levels of patient acceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…In two controlled trials with 227 and 307 patients with schizophrenia,104,114 second-generation antipsychotics could not demonstrate any better quality of life or cost-effectiveness than different types of first-generation antipsychotics during more than a 1-year follow-up. Nonetheless, more recent research and reviews on long-term use of second-generation antipsychotic therapy such as quetiapine115,116 and risperidone104 have shown that it was a more tolerated, acceptable, and satisfactory treatment than the other previously prescribed first-generation antipsychotics. It is recommended that the perceived benefits and other patient-focused outcomes of quetiapine, risperidone, and other newly introduced antipsychotics, compared with other second-generation antipsychotics, be the subject of further research.…”
Section: Patient-focused Perspectivesmentioning
confidence: 99%
“…In two controlled trials with 227 and 307 patients with schizophrenia,104,114 second-generation antipsychotics could not demonstrate any better quality of life or cost-effectiveness than different types of first-generation antipsychotics during more than a 1-year follow-up. Nonetheless, more recent research and reviews on long-term use of second-generation antipsychotic therapy such as quetiapine115,116 and risperidone104 have shown that it was a more tolerated, acceptable, and satisfactory treatment than the other previously prescribed first-generation antipsychotics. It is recommended that the perceived benefits and other patient-focused outcomes of quetiapine, risperidone, and other newly introduced antipsychotics, compared with other second-generation antipsychotics, be the subject of further research.…”
Section: Patient-focused Perspectivesmentioning
confidence: 99%
“…It also has antihistamine and anticholinergic properties. Hypotension is known as a common adverse effect, which is considered to be elicited by inhibition of adrenergic α 1 -receptors 9. However, the mechanism behind quetiapine-induced seizure remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In einem Bericht wird eine Frau erwähnt, bei der unter Raloxifen eine Überempfindlichkeitsreaktion mit Hautausschlag, Ikterus und Leberenzymerhöhung auftrat. 10 In der MORE-Studie beobachtete man in der Raloxifen-Gruppe mehr Fälle von Diabetes mellitus als in der Placebo-Gruppe. 5,6 Mit histologischen Untersuchungen und transvaginalen Sonografien wurde in mehreren Studien abgeklärt, welche Wirkungen Raloxifen auf das Endometrium ausübt.…”
Section: Unerwünschte Wirkungenunclassified